1995
DOI: 10.1016/0895-7061(95)00149-j
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-induced hypertension in the elderly relation to serum calcium and family history of essential hypertension

Abstract: To explore the syndrome of glucocorticoid-induced hypertension in the elderly, we analyzed the clinical findings from 35 patients aged more than 65 years (12 men, 23 women) who received glucocorticoid therapy. Resting blood pressures (BP) were less than 140/90 mm Hg before glucocorticoid therapy, and patients were apparently disease-free apart from the condition for which glucocorticoid therapy was prescribed. Glucocorticoid-induced hypertension is defined as systolic BP more than 160 mm Hg and/or diastolic BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 23 publications
1
23
0
3
Order By: Relevance
“…Th e data show that hypertensive eff ect is dose-dependent and high blood pressure occurs in 80% of patients during corticosteroid therapy [14,15,16]. In our study, hypertension occurred in 28% of patients aft er the administration of prednisone and dexamethasone.…”
Section: Discussionsupporting
confidence: 47%
“…Th e data show that hypertensive eff ect is dose-dependent and high blood pressure occurs in 80% of patients during corticosteroid therapy [14,15,16]. In our study, hypertension occurred in 28% of patients aft er the administration of prednisone and dexamethasone.…”
Section: Discussionsupporting
confidence: 47%
“…17,18 The positive predictive value of atrial fibrillation or flutter has been reported to be as high as 97% in the NRP. 19 We also obtained data from the NRP with regard to hospital procedure codes of cardioversions (treatment code BFFA0 in the Danish treatment classification) within the year after diagnosis of atrial fibrillation or flutter.…”
Section: Cases Of Atrial Fibrillation or Fluttermentioning
confidence: 99%
“…A retrospective meta-analysis reported a significant relationship for hypertension incidence with OR 2.2 (95 % CI 1.4-3.8) [55] among corticosteroid users. Risk may be dose dependent [10], and appears to develop early after initiation of corticosteroids [56].…”
Section: Cardiovascular Diseases Systemic Corticosteroidsmentioning
confidence: 99%